Exploring the potential of local natural organic Dye Sensitizers for Photoelectrochemical cells in Dye Sensitized Solar Cells (Dssc) - Jedol Dayou; Rachel Fran Mansa; Coswald Stephen Sipaut @ Mohd Nasri (Universiti Malaysia Sabah, 2014)
Natural dyes were extracted from the 31 local borneon plant species that were collected from Sabah and Sarawak, Malaysia. The possibility of photon-electron conversion was then assessed based on their absorption ability in the ultraviolet and visible region of wavelength between 200-900nm. In addition, FT-IR analysis was carried out to determine if functional groups exists in their extracts. Furthermore, the pH of the natural dye extracts was measured by using pH meter. Finally, the Dye Sensitized Solar Cells (DSSCs) were assembled and their efficiency measured. It shows the successful conversion from visible sunlight to electricity by using the extracts from local plants as raw natural dye sensitizers in Dye Sensitized Solar Cells (DSSCs) with effiCiency range from 0.004% to 0.19%. This result shows that local natural dyes can be used as sensitizer in DSSCs. However, further investigations are required to improve the efficiency.